2001
DOI: 10.1079/ssr200063
|View full text |Cite
|
Sign up to set email alerts
|

Seed physiological performance of soybeans with altered saturated fatty acid contents

Abstract: Soybean (Glycine max (L.) Merr.) seeds with elevated or reduced percentages of palmitate and elevated percentages of stearate were compared with seeds of typical composition in tests for germination, seedling growth rate and leachate conductivity. In general, seeds with altered compositions did well in these physiological tests, but their vigour tended to be negatively correlated with the percentages of stearate and palmitate in various lipid classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
11
2
Order By: Relevance
“…Seed fatty acid profiles and total seed oil for each genotypic class were consistent with those previously reported (Ruddle et al, 2012)—the primary effect of both the SACPD‐B and SACPD‐C mutations on seed oil composition was an increase in stearic acid and a decrease in oleic acid. Unlike previous studies (Rahman et al, 1997; Wang et al, 2001b), the high seed stearic acid levels due to these two mutations did not significantly reduce germination. Seedling fatty acid composition was affected primarily by the SACPD‐B mutation, with the effect of nearly doubling seedling stearic acid content.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Seed fatty acid profiles and total seed oil for each genotypic class were consistent with those previously reported (Ruddle et al, 2012)—the primary effect of both the SACPD‐B and SACPD‐C mutations on seed oil composition was an increase in stearic acid and a decrease in oleic acid. Unlike previous studies (Rahman et al, 1997; Wang et al, 2001b), the high seed stearic acid levels due to these two mutations did not significantly reduce germination. Seedling fatty acid composition was affected primarily by the SACPD‐B mutation, with the effect of nearly doubling seedling stearic acid content.…”
Section: Discussioncontrasting
confidence: 98%
“…Least squares means of seed fatty acid (g kg -1 ), and seed total oil (g kg -1 ) of 50 lines from the F 2 -derived populations, LLL-05-01 (SACPD-C mutant: fas nc ) × TCJWB03-806-7-19 (SACPD-B mutant: fas2 nc ) and LLL-05-14 (SACPD-C mutant: fas nc ) × TCJWB03-806-7-19. Unlike previous studies (Rahman et al, 1997;Wang et al, 2001b), the high seed stearic acid levels due to these two mutations did not significantly reduce germination. Seedling fatty acid composition was affected primarily by the SACPD-B mutation, with the effect of nearly doubling seedling stearic acid content.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, we have observed that soybeans with elevated stearate percentages have unpredictable and abnormal field germination and low yield. Wang et al (2) showed that seed with altered saturated fatty acid contents generally did fairly well in viability and vigor tests conducted at various temperatures under controlled laboratory conditions, but in a number of instances, seed vigor was negatively correlated with saturate content, especially stearate content.…”
mentioning
confidence: 99%
“…The fatty acid composition of soybean oil completely determines its nutritional value [12], storage compatibility [25], industrial properties [21] and potential food applications [24,28]. Modification of fatty acid composition of soybean oil makes it more competitive in various segments of the food and industrial oil markets [9], and to make it more nutritional [12] has been an important objective of plant breeding and molecular genetics in recent years [29]. Altered fatty acid composition has been developed through traditional plant breeding [33] and application of chemical mutagens [6,10,31] that have extended the range of the five major fatty acid normally found in soybean oil unfortunate.…”
Section: Introductionmentioning
confidence: 99%